Postoperative Magnetic Resonance Imaging after Anterior Cruciate Ligament Reconstruction: An Overview and Practical Step-by-step Guide - Doorschodt, Tom C.; Smithuis, Frank F.; Helmerhorst, Gijs T.T.; Maas, Mario (Seminars in Musculoskeletal Radiology, 2024)
Anterior cruciate ligament (ACL) rupture is a frequently encountered injury among athletes, often requiring surgical intervention to restore knee stability. Magnetic resonance imaging (MRI) after ACL reconstruction is common, especially in the evaluation of clinical complications leading to knee instability, decreased range of motion, or pain. This article provides a detailed overview of normal and abnormal postoperative findings including a practical step-by-step guide for MRI assessment. MRI findings must be correlated with surgical technique, time interval from surgery to imaging, and clinical examination.
Keywords: anterior cruciate ligament reconstruction; postoperative magnetic resonance imaging; complications; step-by-step guide